2016
DOI: 10.1124/jpet.115.229989
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Radioligands for Investigating the Molecular Pharmacology of Melatonin Receptors

Abstract: Melatonin exerts a variety of physiologic activities that are mainly relayed through the melatonin receptors MT 1 and MT 2 Low expressions of these receptors in tissues have led to widespread experimental use of the agonist 2-[125 I]-iodomelatonin as a substitute for melatonin. We describe three iodinated ligands:, which are specific ligands at MT 2 receptors, and125 I]-iodomelatonin with slightly different characteristics. Here, we further characterized these new ligands with regards to their molecular pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Three new iodinated radioligands have been recently characterized for use in the pharmacological characterization and localization of MT receptors (Figure ). These radioligands are as follows: SD6 ( N ‐[2‐(5‐methoxy‐1Hindol‐3‐yl)ethyl]iodoacetamide), S70254 (2‐iodo‐ N ‐2‐[5‐methoxy‐2‐(naphthalen‐1‐yl)‐1H‐pyrrolo[3,2‐b]pyridine‐3‐yl])acetamide and DIV880 2‐(2‐[(2‐iodo‐4,5‐dimethoxyphenyl)methyl]‐4,5‐dimethoxy phenyl) (Legros et al, ; Legros et al, ). [ 125 I]‐SD6 has a similar pharmacological profile to that of 2‐[ 125 I]‐IMLT with the same affinity for MT 1 and MT 2 receptors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three new iodinated radioligands have been recently characterized for use in the pharmacological characterization and localization of MT receptors (Figure ). These radioligands are as follows: SD6 ( N ‐[2‐(5‐methoxy‐1Hindol‐3‐yl)ethyl]iodoacetamide), S70254 (2‐iodo‐ N ‐2‐[5‐methoxy‐2‐(naphthalen‐1‐yl)‐1H‐pyrrolo[3,2‐b]pyridine‐3‐yl])acetamide and DIV880 2‐(2‐[(2‐iodo‐4,5‐dimethoxyphenyl)methyl]‐4,5‐dimethoxy phenyl) (Legros et al, ; Legros et al, ). [ 125 I]‐SD6 has a similar pharmacological profile to that of 2‐[ 125 I]‐IMLT with the same affinity for MT 1 and MT 2 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive pharmacological characterization of these three new radioligands in comparison with 2‐[ 125 I]‐IMLT and [ 3 H]‐MLT on membrane preparations from CHO‐K1 cell lines stably expressing hMT 1 or hMT 2 receptors showed that [ 125 I]‐S70254 and [ 125 I]‐DIV880 mainly differ from 2‐[ 125 I]‐IMLT in their dissociation kinetics, which are faster for [ 125 I]‐S70254 and [ 125 I]‐DIV880 than for 2‐[ 125 I]‐IMLT (Legros et al, ). Interestingly, [ 125 I]‐SD6 labelled only approximately half of the binding sites detected with 2‐[ 125 I]‐IMLT in cells expressing hMT 1 receptors while comparable amounts were detected in cells expressing hMT 2 receptors (Legros et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, CHO‐K1 cells stably expressing human MT 1 (hMT 1 ) or MT 2 (hMT 2 ) were grown to confluence, harvested in PBS buffer (Gibco, Invitrogen, Saint‐Aubin, France) containing 5 mmol/L EDTA, and centrifuged at 1000 g for 20 minutes at 4°C. The resulting pellet was suspended in 5 mmol/L Tris/HCl (pH 7.4) containing 2 mmol/L EDTA and homogenized using Kinematicapolytron.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, combined with a radiotracer, such as the traditional 2‐[ 125 I]‐melatonin, or more recently, the triple‐tritiated melatonin, hundreds of melatonin‐like compounds have been described for their capacity to bind to melatonin receptors (see a chemical review of those molecules in Zlotos et al). More recent studies have given rise to a new generation of compounds that are more selective for one of the MT 1 or MT 2 subtypes . Interestingly, melatonin receptors are slightly different from other receptors, because we were essentially only seeking agonists, as opposed to the traditional search for antagonists as drugs for most of the other GPCRs.…”
Section: The 5d Space Exemplified By Melatonin Receptorsmentioning
confidence: 99%